(untitled) (Global Journal of Human-Social Science, 2013)
The Pareto distribution is to model the income data set of a society. The distribution is appropriate to the situations in which an equilibrium exists in distribution of small to large. There exists many generalization approaches to the distribution. In this paper an effort has been made to compare the applicability of generalized Pareto distribution with Picklands (1975) by using a real life income data set. The model has provided considerable a good fit to the data set. Some well known distributions has been derived as a special case of this model for suitable choice of parameters.